Optimizing Anti-Viral Vaccine Responses: Input from a Non-Specialist - Philip Serwer (MDPI AG, 2020)
Recently, the research community has had a real-world look at reasons for improving vaccine responses to emerging RNA viruses. Here, a vaccine non-specialist suggests how this might be done. I propose two alternative options and compare the primary alternative option with current practice. The basis of comparison is feasibility in achieving what we need: a safe, mass-produced, emerging virus-targeted vaccine on 2-4 week notice. The primary option is the following. (1) Start with a platform based on live viruses that infect bacteria, but not humans (bacteriophages, or phages). (2) Isolate phages (to be called pathogen homologs) that resemble and provide antigenic context for membrane-covered, pathogenic RNA viruses; coronavirus-phage homologs will probably be found if the search is correctly done. (3) Upon isolating a viral pathogen, evolve its phage homolog to bind antibodies neutralizing for the viral pathogen. Vaccinate with the evolved phage homolog by generating a local, non-hazardous infection with the phage host and then curing the infection by propagating the phage in the artificially infecting bacterial host. I discuss how this alternative option has the potential to provide what is needed after appropriate platforms are built.